PENGARUH PEMASARAN MEDIA SOSIAL TERHADAP NIAT PEMBELIAN ULANG DENGAN E-WOM DAN CITRA MEREK SEBAGAI MEDIASI - Yaaro Gaho; Hendy Tannady (POLITEKNIK LP3I JAKARTA, 2026)
Social media marketing is a strategy used by companies to increase interaction with consumers of Haus Indonesia products. Factors such as social media marketing play an important role in increasing sales turnover. This study identifies the influence of electronic word-of-mouth (E-WOM) and brand image on consumer loyalty as a mediator. The sample of this study consisted of 202 Haus Indonesia consumers in the Tangerang City area, selected using purposive sampling. The Structural Equation Model (SEM) was used to analyze the data. The results of the study indicate that social media marketing has a positive influence on electronic word-of-mouth (E-WOM) and brand image, but does not have a significant direct influence on repurchase intention. Meanwhile, E-WOM and brand image act as mediators that strengthen the impact of social media marketing, thereby indirectly increasing consumers' repurchase intention. Managerial implications for enhancing repurchase intention include the need for the company to promote Indonesian products by offering a 50% discount to customers who follow the Haus Indonesia social media account. Additionally, it is important for Haus Indonesia to establish a dedicated team responsible for consolidating and responding to comments or complaints on social media quickly and professionally to maintain a positive company image and prevent issues from escalating. This study recommends that future research consider adding other variables such as gender and use a combination of qualitative and quantitative methods.